PENERAPAN PEMBELAJARAN TEKNIK VOKAL MELALUI LAGU ENGGUNG KEPADA PESERTA DIDIK PADUAN SUARA DI SMP NEGERI 8 DENPASAR - Siregar, Vivi Anita; Sumerjana, Ketut; Wiyati, Wahyu Sri (MELODIOUS : JOURNAL OF MUSIC, 2024)
This research was motivated by the low level of vocal technique mastery of choir students at SMP Negeri 8 Denpasar. This research was created with the aim of explaining the process of applying vocal technique learning to the Enggung song and to improve the vocal technique of choir students at SMP Negeri 8 Denpasar. The research method used was through interviews, document study and observation. The research subjects were students who were registered as extracurricular members of the choir at SMP Negeri 8 Denpasar. The target achievement in vocal learning activities is to improve vocal technique in performing Enggung songs, so that students can understand and apply the material presented well by the teacher. Observations of students show that there are several problems caused by time and students' learning ability, such as: Students' lack of learning ability so that students have difficulty directly practicing the material that has been given, limited time so that the knowledge they receive cannot be realized effectively, as well as lack of practice.